2020
DOI: 10.3390/nano10040775
|View full text |Cite
|
Sign up to set email alerts
|

Down-Shifting and Anti-Reflection Effect of CsPbBr3 Quantum Dots/Multicrystalline Silicon Hybrid Structures for Enhanced Photovoltaic Properties

Abstract: Over the past couple of decades, extensive research has been conducted on silicon (Si) based solar cells, whose power conversion efficiency (PCE) still has limitations because of a mismatched solar spectrum. Recently, a down-shifting effect has provided a new way to improve cell performances by converting ultraviolet (UV) photons to visible light. In this work, caesium lead bromide perovskite quantum dots (CsPbBr3 QDs) are synthesized with a uniform size of 10 nm. Exhibiting strong absorption of near UV light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In the same wavelength, the absorption of the cell has an average enhancement factor of 5.76 ± 0.01%, in the presence of the thin film down-shifting layer. These results compare very well with those described in the work of Cao et al [ 1 ], on a similar CsPbBr 3 NCs thin film system for down-shifting in microcrystalline silicon solar cells. The paper demonstrated that, at 320 nm, there is an enhancement factor of 27% in the EQE and of 4% in the absorption of the solar cell.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the same wavelength, the absorption of the cell has an average enhancement factor of 5.76 ± 0.01%, in the presence of the thin film down-shifting layer. These results compare very well with those described in the work of Cao et al [ 1 ], on a similar CsPbBr 3 NCs thin film system for down-shifting in microcrystalline silicon solar cells. The paper demonstrated that, at 320 nm, there is an enhancement factor of 27% in the EQE and of 4% in the absorption of the solar cell.…”
Section: Resultssupporting
confidence: 90%
“…Silicon based photovoltaic cells have been extensively explored and have become the dominant photovoltaic systems. Silicon is a widely abundant and non-pollutant element, reaching, in crystalline silicon solar cells, very good efficiency, up to 26.8% [ 1 , 2 , 3 ]. Nevertheless, silicon based solar cells, including nanocrystalline silicon solar cells, display low spectral response for high energy photons (in the blue and UV range), which are not converted by the device and raise thermalization issues [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…198 Recently, the down-shiing effect has been proven to be able to increase the solar cell performance by converting UV light to visible light. 199 Lanthanide down-conversion material, with the ability to absorb UV light and re-emit it in the visible region, was added to the ZnO electron transport layer, so that the re-emitted light matches the absorption energy level of the active layer material. 200 Here, Eu(TTA) 3 phen (ETP) was used as the downconversion material, with PTB7-Th:PC 71 BM as the active layer, resulting in a cell with PCE of 9.22% and 70% higher stability compared to the cell with pristine ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…The converter can be obtained by simply spin coating AIP QDs on the surface of SCs. For example, Cao et al 162 synthesized CsPbBr 3 QDs with the uniform size of 10 nm, and spin coated the colloidal QDs on the surface of commercial mc-Si SCs to obtain CsPbBr 3 QDs/mc-Si hybrid SCs. Compared with mc-Si SCs, the external quantum efficiency of CsPbBr 3 QDs/mc-Si SCs is signicantly improved in the wavelength range of 300-500 nm and 700-1100 nm, and the maximum PCE of SCs is 14.52%.…”
Section: Converters For Conventional Scsmentioning
confidence: 99%